Aidez moi s'il vous plaît!
Factorisez les expressions suivantes : ( J'comprends rien)

D(x)=(2x+3)(x-7)+(2x+3)(-4x+5)
E(x)=4x²-4x+1
F(x)=(x-1)(2x+4)-(x-1)(x+5)+2(x-1)
G(x)=9(x+1)²-16
H(x)=(x+3)²-3(x+3)(-2x+4)

Merci

1

Réponses

2014-09-28T14:15:54+02:00
D(x)=(2x+3)(x-7)+(2x+3)(-4x+5)
D(x)=(2x+3)(x-7-4x+5)
D(x)=(2x+3)(-3x-2)

E(x)=4x²-4x+1
(a - b)
² = a² - 2ab + b² 
a = 2x
b=1
E(x) =(2x-1)
²

F(x)=(x-1)(2x+4)-(x-1)(x+5)+2(x-1)
F(x)=(x-1)(2x+4-x-5+2)
F(x)=(x-1)(x+1)

G(x)=9(x+1)²-16
9(x+1)
² = (3x+3)² 
G(x)= (3x+3)
² - 16
a
² - b² = (a + b)(a - b)
G(x) = (3x+3+4)(3x+3-4)
G(x) = (3x+7)(3x-1)

H(x)=(x+3)²-3(x+3)(-2x+4)
H(x)=(x+3)(x+3-3(-2x+4))
H(x)=(x+3)(x+3+6x-12)
H(x)=(x+3)(7x-9)